2015
DOI: 10.18632/oncotarget.4945
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glucose-6-phosphate dehydrogenase sensitizes cisplatin-resistant cells to death

Abstract: The mechanisms of cisplatin resistance, one of the major limitations of current chemotherapy, has only partially been described. We previously demonstrated that cisplatin-resistant ovarian cancer cells (C13), are characterized by reduced mitochondrial activity and higher glucose-dependency when compared to the cisplatin-sensitive counterpart (2008). In this work we further characterized the role of metabolic transformation in cisplatin resistance. By using transmitochondrial hybrids we show that metabolic repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 47 publications
9
106
0
Order By: Relevance
“…Several agents are known to sensitize cancer cells to cisplatin, one of which is 6-AN (49). This effect is primarily due to the action of 6-amino-NAD(P+), which results in intracellular cisplatin enrichment and the accumulation of plasma tumor DNA adducts (50). Pretreatment with 6-AN has been demonstrated to sensitize different tumor cells to cisplatin cytotoxicity, even cisplatin-resistant cells; this may explain the synergistic effects of 6-AN and cisplatin on bladder cancer cells (49,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several agents are known to sensitize cancer cells to cisplatin, one of which is 6-AN (49). This effect is primarily due to the action of 6-amino-NAD(P+), which results in intracellular cisplatin enrichment and the accumulation of plasma tumor DNA adducts (50). Pretreatment with 6-AN has been demonstrated to sensitize different tumor cells to cisplatin cytotoxicity, even cisplatin-resistant cells; this may explain the synergistic effects of 6-AN and cisplatin on bladder cancer cells (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…This effect is primarily due to the action of 6-amino-NAD(P+), which results in intracellular cisplatin enrichment and the accumulation of plasma tumor DNA adducts (50). Pretreatment with 6-AN has been demonstrated to sensitize different tumor cells to cisplatin cytotoxicity, even cisplatin-resistant cells; this may explain the synergistic effects of 6-AN and cisplatin on bladder cancer cells (49,50). However, it has also been reported that 6-AN may cause neurotoxicity or hematological toxicity under certain conditions (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been shown to sensitive tumor cells to chemotherapeutics41. One study showed that inhibition of G6PDH, the committed step of the pentose phosphate pathway that is regulated by the NADPH/NADP ratio, sensitizes cisplatin-resistant cancer cells42. Previous work has shown that the PKM2 isozyme implicated in inducing the Warburg metabolic phenotype also responds to reactive oxygen species by increasing oxidative stress resistance through increasing pentose phosphate pathway flux43.…”
Section: Discussionmentioning
confidence: 99%
“…For ex am ple, in ovar ian can cer, one of the most lethal can cers world wide, cis platin re sis tant cells dis played in creased OX PHOS and ROS lev els com pared to sen si tive cells, and this phe no type was re versed upon phar ma co log i cal in hi bi tion of mi to chon dr ial OX PHOS or ROS scav eng ing [133]. The op po site phe nom e non, chemore sis tance by a low ox ida tive me tab o lism, has been iden ti fied as well [134,135]. De spite that these two types of meta bolic chemore sis tance may ap pear to be op po site, they both act through a de creased ca pa bil ity of mi to chon dria to gen er ate ROS, ei ther by up reg u lat ing an tiox i dant de fenses in a high OX PHOS con text [136] or by de creas ing ROS gen er a tion at the elec tron trans port chain when OX PHOS is low.…”
Section: Metabolic Regulation Of Cancer Cell Deathmentioning
confidence: 97%